The Global Smooth Solution for Landau-Lifshitz-Maxwell Equation Without Dissipation (Journal of Partial Differential Equations, 1998)
In this paper, the global existence of a unique smooth solution for the Landau-Lifshitz-Maxwell equations of the ferromagnetic spin chain without dissipation in n (1 ≤ n ≤ 2) dimensions is established by using the viscosity elimination method.
Keywords: Landau-Lifsbitz-Maxwell equation; global smooth solution